2014
DOI: 10.1177/0020764014562051
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stigmatising attitudes towards people with substance use disorders between the general public, GPs, mental health and addiction specialists and clients

Abstract: The general public and GPs expressed more social distance and were more negative in their expectations about rehabilitation opportunities, compared to mental health and addiction specialists and clients. Although stigmatising attitudes were prevalent across all groups, no striking differences were found between stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 39 publications
5
90
0
3
Order By: Relevance
“…Such an instrument is highly needed given the enormous variation in perceptions of addiction and its possible relationship with attitude and stigma. Since patients with addiction often perceive stigma and negative attitudes, also from health care professionals [7, 45], instruments that can help identify potential factors that may contribute to such stigma, like illness perceptions, are of great relevance. Given its acceptable psychometric properties, the IPQ-A may be such an instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Such an instrument is highly needed given the enormous variation in perceptions of addiction and its possible relationship with attitude and stigma. Since patients with addiction often perceive stigma and negative attitudes, also from health care professionals [7, 45], instruments that can help identify potential factors that may contribute to such stigma, like illness perceptions, are of great relevance. Given its acceptable psychometric properties, the IPQ-A may be such an instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal health care for persons using drugs may be explained by health professionals’ negative attitudes toward these patients, as shown by a systematic review and surveys assessing stigma in this context. 5354 …”
Section: Discussionmentioning
confidence: 99%
“…Corker et al () concluded that family or friends were affected by anti‐stigma campaigns more than health professionals, and called for anti‐stigma interventions targeted to specific groups. Van Boekel, Brouwers, Van Weeghel, and Garretsen () compared members of the general public, general practitioners, mental health and addiction specialists, and clients in drug treatments. Across several stigma‐related variables, members of the general public held the most negative views, followed by both groups of health professionals, with clients holding the most positive attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biological models often undergird attributions to noncontrollable causes and such models heighten a sense of discrete boundaries between stigmatized groups and the nonstigmatized, which in turn engender prejudice (e.g., Corrigan et al, ; Haslam & Levy, ; Prentice & Miller, ). Consequently, we aimed to assess recent claims that attribution theory describes stigma in this domain well (Van Boekel et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation